Survive Amidst the Competition of Private Universities by Maximizing Brand Image and Interest in Studying - Nasib Nasib; Muhammad Fauzan Azhmy; Septa Diana Nabella; Rusiadi Rusiadi; Ahmad Fadli (STAI Hubbulwathan Duri, 2022)
Increasing the demand for college provides financial benefits for private universities to survive amid intense competition. The ability to increase interest in college, especially for prospective new students, is largely determined by accreditation, telemarketing, and the university's brand image. The main study in this research is to analyze the brand image model and college interest which is influenced by accreditation and telemarketing. The analytical method in this study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS). The population in this study was 100 students of class XII in SMA/SMK/Private Aliyah in the city of Medan. The sampling technique used was accidental sampling where 100 class XII students were the main target. Data collection techniques using a questionnaire (questionnaire). The results showed that (1) directly accreditation was not significant to brand image, (2) telemarketing directly had a significant effect on brand image, (3) directly accreditation had a significant effect on college interest, (4) telemarketing directly had a significant effect on interest college interest, (5) directly brand image has a significant effect on college interest, (6) indirectly brand image has no role in mediating accreditation of college interest and (7) brand image indirectly has a role in mediating telemarketing on college interest.